(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2023)
As advertisers found multiple methods to approach the audience to their advertisement, emotional appeal was one of the most popular ones. In addition, many studies have defined cultural factors’ influence on emotional engagement in diverse cultures but little in collectivist cultures like Vietnam. In this paper, we examine how advertisers apply cultural elements to evoke emotional appeal in some popular Vietnam ads and how viewers could provoke empathy. Content analysis was employed as the primary research method in this study to demonstrate the impact of specific cultural characteristics on whether or not advertising elicits empathy in the audience. We have case studies with texts and pictures with cultural undertones that are thought to arouse viewers’ empathy. The quantitative data was also collected via a sample survey for measurement and classification. The survey was conducted to examine how participants, who are 15-40 years old, and their emotions were affected by cultural advertising. Following the view of interdependently themed videos, each participant responded to a series of questions on their feelings about the corresponding advertising. The results showed that culture influences the emotional component of advertising. Vietnam, a collectivist country, possessed a high degree of empathy. The paper’s results partly be used in practice, particularly in designing advertisements with a broad target audience in collectivist cultures.